Plan de mejoramiento para el área de servicio y atención al cliente, en la empresa “Frutas y Verduras Johanna” en Santiago de Cali, Valle del Cauca (2014)
“Frutas y verduras Johanna” is a family business that has a history of over 10 years in the market for which is dedicated to the marketing of fruit and vegetables and of excellent quality. In recent years, there has been an increase in competition with similar businesses and thus a decrease in the volume of sales that continue, could threaten the viability of the company. With the completion of this project will make an improvement plan for the area of customer service and the company, based on an assessment of your current situation and an analysis of competition, in order to identify which aspects need improvement to attract customers and increase sales levels. Project development is based on studies made at the institution which will allow investigations rely on improvement plans. As data collection instrument used was a survey which considers aspects such as competition, prices, quality, customer tastes and sales strategies. Their analysis will identify key issues for the implementation of the improvement plan. They present clear alternatives to ensure an improvement in their operation, recommending strategies to ensure the permanence of the business in the market.